Dinamika Modal Sosial dan Ketahanan Sosial Rumah Tangga Pedagang Sayur Keliling di Mahakarya Kampung 2 Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Oktaviani, Osi; Zusmelia, Zusmelia; Irwan, Irwan (Program Studi Tadris IPS Fakultas tarbiyah IAIN Kudus, 2021)
The background of this research is based on data analysis of social capital owned by mobile vegetable traders who are able to survive in household social security. This study aims to analyze the dynamics of social capital and social resilience of mobile vegetable merchant households in Mahakarya Kampung 2, Luhak Nan Duo District, West Pasaman Regency. This research uses a qualitative approach by collecting observational data, in-depth interviews and document studies. The results of this study indicate that the dynamics of mobile vegetable traders are 1) The network built between traders and customers has 2) The trust of mobile vegetable traders is to allow customers to borrow. 3) Norms or rules for paying debts which were initially only allowed 2 days, now customers are allowed to pay for 1 week. The social resilience of the mobile vegetable merchant household is the fulfillment of daily.